The role of permanent lectors, acolytes, and deacons in the service of the Church community - DYDUCH, JAN (Prawo Kanoniczne, 2017)
The leading idea of the Second Vatican Council was the call for cooperation between the laity and the clergy. The cooperation in question is a reinforcement of the community of the Church, where one can find both: the equality of the members, and diversity of the functions. This cooperation appears, e.g., as a participation of all the Faithfull in in the sacred liturgy of the Church. In the liturgy the permanent lectors, acolytes, and deacons play an important role. The functions were re-instituted according to directions provided by the council and called to the service of the Church.